A sustained release pharmaceutical formulation and a method for preparing the same
Patent Information
- Application Number
- CN202611449499.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-17
- Publication Date
- 2026-10-30
AI Technical Summary
公开号为CN1994283A的专利申请公开了一种尼可地尔缓释制剂,使用含水量较高的亲水凝胶骨架材料达到缓释效果,但仅能缓释12小时,难以达到24小时长效缓释目标
1、本发明采用乳液模板法原位构建孔道网络,孔道尺寸均一、空间分布均匀,从结构上解决了蜡质骨架缓释制剂突释与释放完全性的矛盾;2小时药物释放量控制在8.7%至11.9%,24小时药物释放率达到92%以上,实现了低突释与高释放完全性的统一。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of pharmaceutical formulation technology, specifically to a sustained-release pharmaceutical formulation and its preparation method. Background Technology
[0002] Oral sustained-release formulations play an important role in the long-term treatment of chronic diseases due to their ability to reduce the frequency of administration, decrease fluctuations in blood drug concentrations, and improve patient compliance. Currently, oral sustained-release formulations mainly include matrix-based, membrane-controlled, and osmotic pump-based technologies. Among them, wax-based matrix sustained-release formulations are widely used in industrial production due to their relatively simple preparation process, insensitivity to gastrointestinal pH, and good reproducibility of drug release.
[0003] Existing wax-based sustained-release formulations typically use hydrophobic wax materials such as carnauba wax, stearic acid, hydrogenated castor oil, and glyceryl behenate as the matrix. The drug is dispersed within the matrix and released through diffusion through pores and matrix dissolution. To regulate the release rate, porogens such as polyethylene glycol, sugars, and polyvinylpyrrolidone (PVP) are often added to the formulation. Patent application CN101002739A discloses a sustained-release tablet and its preparation method, using a combination of a hydrophilic gel matrix material and a soluble matrix material to prepare the sustained-release formulation. Patent application CN1994283A discloses a nicorandil sustained-release formulation, using a hydrophilic gel matrix material with high water content to achieve a sustained-release effect, but it only provides sustained release for 12 hours, failing to achieve the 24-hour long-term sustained-release target.
[0004] Existing wax-based sustained-release technologies have the following limitations: The pore-forming agent is added through physical mixing with the wax material, resulting in uneven distribution of the pore-forming agent within the matrix and a high content of pore-forming agent on the surface. This leads to a significant burst release effect in the initial stage of the formulation's contact with the release medium, posing a safety hazard of excessive blood drug concentration in clinical applications. If the amount of pore-forming agent is reduced to decrease burst release, the internal pores of the formulation become insufficient, leading to a sharp decline in the drug release rate in the later stages, incomplete release, and reduced bioavailability. Conventional preparation processes such as melt granulation and wet granulation are difficult to precisely control the size and distribution of pores, resulting in significant batch-to-batch differences in release behavior.
[0005] The aforementioned issues constitute the core technical contradiction that has long existed in the field of wax-based sustained-release formulations: it is difficult to simultaneously achieve burst release control and complete release, and those skilled in the art cannot effectively resolve this contradiction through conventional formulation optimization methods. Summary of the Invention
[0006] The primary objective of this invention is to provide a sustained-release pharmaceutical preparation and its preparation method.
[0007] A further object of the present invention is to provide a sustained-release pharmaceutical formulation, based on total mass, prepared from the following components in the following mass percentages: 20% to 40% active pharmaceutical ingredient, 35% to 60% waxy matrix material, 2% to 5% emulsifier, 5% to 10% pore-forming agent, 5% to 15% filler, and 0.5% to 2% lubricant; wherein the waxy matrix material is composed of glyceryl behenate and cetyl alcohol in a mass ratio of 2:1 to 4:1; the emulsifier is sorbitan monostearate; the pore-forming agent is polyethylene glycol 6000; the sustained-release pharmaceutical formulation has a uniformly distributed pore structure with an average pore diameter of 5 μm to 30 μm and a pore diameter variation coefficient of less than 25%, and the pore walls are coated with the pore-forming agent.
[0008] Preferably, the mass ratio of behenicol to cetyl alcohol in the waxy skeleton material is 2.5:1 to 3.5:1.
[0009] Preferably, the active pharmaceutical ingredient is metformin hydrochloride.
[0010] Preferably, the filler is microcrystalline cellulose and the lubricant is magnesium stearate.
[0011] A method for preparing the sustained-release pharmaceutical formulation as described in claim 1, comprising the following steps: Step 1, Oil phase preparation: Weigh the prescribed amounts of glyceryl behenate and cetyl alcohol, place them in a sealed container heated in a water bath, heat to 78°C to 85°C, and stir until completely melted; add the prescribed amounts of active pharmaceutical ingredient and sorbitan monostearate, and stir at 300 r / min to 500 r / min for 20 min to 30 min to obtain a uniformly dispersed oil phase mixture; Step 2, Aqueous Phase Preparation: Weigh the prescribed amount of polyethylene glycol 6000, dissolve it in purified water to prepare a 20% to 35% (w / w) polyethylene glycol 6000 aqueous solution, heat to 75°C to 80°C and maintain the temperature to obtain an aqueous solution; wherein, the mass of purified water added is 30% to 50% of the total mass of the waxy skeleton material; Step 3, emulsion preparation: Under the temperature conditions of 78℃ to 82℃, the aqueous phase solution obtained in step 2 is slowly added dropwise to the oil phase mixture obtained in step 1. The dropwise addition process is accompanied by high-speed shear emulsification, with a shear rate of 8000 r / min to 12000 r / min. After the aqueous phase is completely added, shearing continues for 5 min to 10 min to obtain a water-in-oil emulsion. Step 4, gradient curing: Transfer the emulsion obtained in Step 3 to a cooling container equipped with a stirrer, turn on the stirrer at a speed of 80 r / min to 150 r / min; reduce the system temperature from 78°C to 55°C at a cooling rate of 1.5°C to 2.5°C per minute, and stir for 10 min to 15 min; continue to reduce the system temperature from 55°C to 35°C at a cooling rate of 0.8°C to 1.2°C per minute, and stir for 20 min to 30 min to obtain a semi-cured granular material; Step 5, Granulation and Drying: The semi-cured granular material obtained in Step 4 is granulated through a 24-mesh sieve and qualified granules are collected; the granules are placed in a hot air circulating oven and dried at 40℃ to 45℃ for 4 to 6 hours until the moisture content of the granules is less than 2.0%, thus obtaining porous waxy skeleton granules. Step 6, Total Mixing and Tableting: Weigh the prescribed amount of filler and lubricant, mix them evenly with the porous waxy matrix particles obtained in Step 5, and compress them into tablets to obtain the sustained-release pharmaceutical preparation.
[0012] Preferably, the shear rate of high-speed shear emulsification in step three is 9000 r / min to 11000 r / min, and the shearing time is 6 min to 8 min.
[0013] Preferably, in step four, the cooling rate in the first stage is 1.8°C to 2.2°C per minute, and the cooling rate in the second stage is 0.9°C to 1.1°C per minute.
[0014] Preferably, the mass concentration of the polyethylene glycol 6000 aqueous solution in step two is 23% to 28%.
[0015] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention uses an emulsion template method to construct a pore network in situ, resulting in uniform pore size and spatial distribution. This structurally resolves the contradiction between burst release and complete release in wax-based sustained-release formulations. The drug release rate is controlled between 8.7% and 11.9% in 2 hours, and the drug release rate reaches over 92% in 24 hours, achieving a balance between low burst release and high complete release.
[0016] 2. The present invention uses a gradient curing process with programmed cooling to solidify the wax skeleton layer by layer around the emulsion droplets, ensuring the integrity and uniformity of the pore structure; the two-stage cooling strategy avoids pore collapse or deformation caused by rapid cooling and improves the consistency of batch release behavior.
[0017] 3. The preparation process of this invention is simple and does not require complex equipment. It can be achieved with conventional melting equipment and shear emulsification equipment, making it easy to scale up for industrial production.
[0018] 4. The release behavior of the formulation of the present invention is less affected by the pH value and peristalsis intensity of the gastrointestinal tract, has good in vitro-in vivo correlation, and has stable blood drug concentration and high safety in clinical application. Detailed Implementation
[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] Invention Mechanism: This invention uses a water-in-oil emulsion as a structural template. While the waxy framework material is in a molten state, an aqueous phase containing a pore-forming agent is uniformly dispersed in the form of tiny droplets within a continuous oil phase. Subsequently, a programmed cooling process causes the waxy framework material to gradually solidify around the droplets. During the framework solidification process, the droplets are sealed in situ, forming a pore template. After drying to remove moisture, the pore-forming agent dissolved in the aqueous phase is deposited on the inner wall of the pores, forming a uniform pore network with an inner wall rich in hydrophilic substances.
[0021] The aforementioned pore network has the following structural characteristics: the pores are approximately spherical or ellipsoidal in shape, with uniform size distribution, an average pore diameter ranging from 5 μm to 30 μm, and a pore diameter variation coefficient of less than 25%; the pores are uniformly distributed in the three-dimensional space of the framework, without surface enrichment or central depletion; the inner walls of the pores are coated with a hydrophilic pore-forming agent, which dissolves rapidly upon contact with the release medium, forming continuous diffusion channels.
[0022] The drug release process is divided into three stages: In the initial stage, the release medium enters the pores through the surface pores. After the pore-forming agent dissolves in the pores, the medium continues to penetrate inward. Due to the limited number and small size of the surface pores, the initial drug release rate is slow, and the burst release effect is effectively suppressed. In the intermediate stage, as the medium penetrates deeper, a large number of pores inside the matrix are connected, and the drug diffuses outward through the pore network. At the same time, the waxy matrix undergoes slow erosion. The diffusion path and erosion work together to maintain a stable release rate. In the final stage, the waxy matrix further dissolves and thins, and the originally isolated pores gradually merge to form larger diffusion channels. The drug release rate is maintained at a reasonable level, avoiding the phenomenon of a sharp drop in the release rate in the later stage of conventional waxy matrix formulations, and ensuring complete release.
[0023] The above structure is fundamentally different from the waxy skeleton of conventional mixed porogens: in conventional mixing methods, porogen particles are randomly distributed, the probability of contact between particles is low, it is difficult to form a continuous diffusion network, and the high proportion of surface porogens leads to obvious burst release; while the pore network constructed in situ by the emulsion template method of this invention has uniform pore size, uniform spatial distribution, and hydrophilic inner wall, achieving a balance between low burst release in the initial stage and high release rate in the final stage. This effect is something that those skilled in the art cannot expect through conventional formulation design.
[0024] Raw material source: Metformin hydrochloride, pharmaceutical grade, purity greater than or equal to 99.0%, CSPC Ouyi Pharmaceutical Co., Ltd.
[0025] Glyceryl behenate (with disorbate as the main component), product name Compritol 888 ATO, melting point range 69°C to 74°C, HLB value approximately 2, manufactured by JAFCO (Shanghai) Trading Co., Ltd.
[0026] Cetyl alcohol, pharmaceutical grade, melting point range 46℃ to 50℃, hydroxyl value 216mg / g to 234mg / g, Sinopharm Chemical Reagent Co., Ltd.
[0027] Sorbitan monostearate, trade name Span 60, pharmaceutical grade, HLB value 4.7, saponification value 147 mg / g to 157 mg / g, Nanjing Well Pharmaceutical Group Co., Ltd.
[0028] Polyethylene glycol 6000, pharmaceutical grade, average molecular weight 5400 to 7800, hydroxyl value 17 mg / g to 22 mg / g, Sinopharm Chemical Reagent Co., Ltd.
[0029] Microcrystalline cellulose, model SH-102 (formerly PH102, but corrected because the product model of Anhui Shanhe Pharmaceutical Excipients Co., Ltd. is SH-102 series, while PH102 is a name given by a foreign manufacturer and cannot be reliably obtained through the corresponding channels), particle size distribution 50μm to 150μm, moisture content less than or equal to 5.0%, Anhui Shanhe Pharmaceutical Excipients Co., Ltd.
[0030] Magnesium stearate, pharmaceutical grade, conforming to the Chinese Pharmacopoeia 2020 edition, Part IV standard, with magnesium oxide content of 6.8% to 8.3%, Anhui Shanhe Pharmaceutical Excipients Co., Ltd. Example 1:
[0031] Raw material formula: Metformin hydrochloride 80g, glyceryl behenate 75g, cetyl alcohol 25g, sorbitan monostearate 6g, polyethylene glycol 6000 15g, microcrystalline cellulose 16g, magnesium stearate 3g.
[0032] Preparation process: Step 1, oil phase preparation: Weigh 75g of behenicol and 25g of cetyl alcohol, place them in a sealed container heated in a water bath, heat to 80℃, and stir until completely melted; add 80g of metformin hydrochloride and 6g of sorbitan monostearate, and stir for 25min at 400r / min to obtain a uniformly dispersed oil phase mixture.
[0033] Step 2, Aqueous phase preparation: Weigh 15g of polyethylene glycol 6000, dissolve it in 45g of purified water to prepare a 25% (w / w) polyethylene glycol 6000 aqueous solution, heat it to 78℃ and keep it warm to obtain an aqueous solution.
[0034] Step 3, emulsion preparation: At a temperature of 80℃, the aqueous phase solution is slowly added dropwise to the oil phase mixture. The dropwise addition process is accompanied by high-speed shear emulsification with a shear rate of 10000 r / min. After the aqueous phase is completely added, shearing continues for 8 min to obtain a water-in-oil emulsion.
[0035] Step 4, gradient curing: Transfer the emulsion to a cooling container equipped with a stirrer, turn on the stirrer at a speed of 120 r / min; reduce the system temperature from 78℃ to 55℃ at a cooling rate of 2.0℃ per minute, and keep stirring at this temperature for 12 min; continue to reduce the system temperature from 55℃ to 35℃ at a cooling rate of 1.0℃ per minute, and keep stirring at this temperature for 25 min to obtain semi-cured granular material.
[0036] Step 5, Granulation and Drying: The semi-cured granular material is granulated through a 24-mesh sieve and qualified granules are collected; the granules are placed in a hot air circulating oven and dried at 42℃ for 5 hours until the moisture content of the granules is 1.6%, thus obtaining porous waxy skeleton granules.
[0037] Step 6, total mixing and tableting: Weigh 16g of microcrystalline cellulose and 3g of magnesium stearate, mix them evenly with porous waxy skeleton particles, compress them into tablets, and the tablet weight is 220mg to obtain sustained-release tablets.
[0038] The sustained-release tablets obtained in this embodiment have a hardness of 8.2 kgf, a friability of 0.42%, and a content uniformity A+1.8S value of 7.3. Example 2:
[0039] Raw material formula: Metformin hydrochloride 70g, glyceryl behenate 84g, cetyl alcohol 36g, sorbitan monostearate 8g, polyethylene glycol 6000 20g, microcrystalline cellulose 20g, magnesium stearate 2g.
[0040] Preparation process: Step 1, oil phase preparation: Weigh 84g of behenicol and 36g of cetyl alcohol, place them in a sealed container heated in a water bath, heat to 82℃, and stir until completely melted; add 70g of metformin hydrochloride and 8g of sorbitan monostearate, and stir for 22min at 450r / min to obtain a uniformly dispersed oil phase mixture.
[0041] Step 2, Aqueous phase preparation: Weigh 20g of polyethylene glycol 6000, dissolve it in 60g of purified water to prepare a 25% (w / w) polyethylene glycol 6000 aqueous solution, heat it to 79℃ and keep it warm to obtain an aqueous solution.
[0042] Step 3, emulsion preparation: At a temperature of 81℃, the aqueous phase solution is slowly added dropwise to the oil phase mixture. The dropwise addition process is accompanied by high-speed shear emulsification with a shear rate of 9500 r / min. After the aqueous phase is completely added, shearing continues for 7 min to obtain a water-in-oil emulsion.
[0043] Step 4, gradient curing: Transfer the emulsion to a cooling container equipped with a stirrer, turn on the stirrer at a speed of 100 r / min; reduce the system temperature from 79℃ to 55℃ at a cooling rate of 1.9℃ per minute, and stir for 14 min; continue to reduce the system temperature from 55℃ to 35℃ at a cooling rate of 1.1℃ per minute, and stir for 22 min to obtain semi-cured granular material.
[0044] Step 5, Granulation and Drying: The semi-cured granular material is granulated through a 24-mesh sieve, and qualified granules are collected; the granules are placed in a hot air circulating oven and dried at 43℃ for 5.5 hours until the moisture content of the granules is 1.4%, thus obtaining porous waxy skeleton granules.
[0045] Step 6, total mixing and tableting: Weigh 20g of microcrystalline cellulose and 2g of magnesium stearate, mix them evenly with porous waxy matrix particles, compress them into tablets, and the tablet weight is 240mg to obtain sustained-release tablets.
[0046] The sustained-release tablets obtained in this embodiment have a hardness of 7.9 kgf, a friability of 0.48%, and a content uniformity A+1.8S value of 8.1. Example 3:
[0047] Raw material formula: Metformin hydrochloride 88g, glyceryl behenate 68g, cetyl alcohol 22g, sorbitan monostearate 5g, polyethylene glycol 6000 18g, microcrystalline cellulose 16g, magnesium stearate 3g.
[0048] Preparation process: Step 1, oil phase preparation: Weigh 68g of behenicol and 22g of cetyl alcohol, place them in a sealed container heated in a water bath, heat to 79°C, and stir until completely melted; add 88g of metformin hydrochloride and 5g of sorbitan monostearate, and stir for 28 minutes at 380r / min to obtain a uniformly dispersed oil phase mixture.
[0049] Step 2, Aqueous phase preparation: Weigh 18g of polyethylene glycol 6000, dissolve it in 42g of purified water to prepare an aqueous solution of polyethylene glycol 6000 with a mass concentration of approximately 26.5%, heat it to 76℃ and keep it warm to obtain an aqueous solution.
[0050] Step 3, emulsion preparation: At a temperature of 79℃, the aqueous phase solution is slowly added dropwise to the oil phase mixture. The dropwise addition process is accompanied by high-speed shear emulsification with a shear rate of 10500 r / min. After the aqueous phase is completely added, shearing continues for 6 min to obtain a water-in-oil emulsion.
[0051] Step 4, gradient curing: Transfer the emulsion to a cooling container equipped with a stirrer, turn on the stirrer at a speed of 130 r / min; reduce the system temperature from 77℃ to 55℃ at a cooling rate of 2.1℃ per minute, and keep stirring at this temperature for 11 min; continue to reduce the system temperature from 55℃ to 35℃ at a cooling rate of 0.9℃ per minute, and keep stirring at this temperature for 28 min to obtain semi-cured granular material.
[0052] Step 5, Granulation and Drying: The semi-cured granular material is granulated through a 24-mesh sieve and qualified granules are collected; the granules are placed in a hot air circulating oven and dried at 41°C for 6 hours until the moisture content of the granules is 1.7%, thus obtaining porous waxy skeleton granules.
[0053] Step 6, total mixing and tableting: Weigh 16g of microcrystalline cellulose and 3g of magnesium stearate, mix them evenly with porous waxy skeleton particles, compress them into tablets, and the tablet weight is 220mg to obtain sustained-release tablets.
[0054] The sustained-release tablets obtained in this embodiment have a hardness of 8.3 kgf, a friability of 0.41%, and a content uniformity A+1.8S value of 7.8. Example 4:
[0055] Raw material formula: Metformin hydrochloride 75g, glyceryl behenate 84g, cetyl alcohol 21g, sorbitan monostearate 7g, polyethylene glycol 6000 12g, microcrystalline cellulose 18g, magnesium stearate 3g.
[0056] Preparation process: Step 1, oil phase preparation: Weigh 84g of behenicol and 21g of cetyl alcohol, place them in a sealed container heated in a water bath, heat to 81℃, and stir until completely melted; add 75g of metformin hydrochloride and 7g of sorbitan monostearate, and stir for 24min at 420r / min to obtain a uniformly dispersed oil phase mixture.
[0057] Step 2, Aqueous phase preparation: Weigh 12g of polyethylene glycol 6000, dissolve it in 40g of purified water to prepare an aqueous solution of polyethylene glycol 6000 with a mass concentration of approximately 23.1%, heat it to 77℃ and keep it warm to obtain an aqueous solution.
[0058] Step 3, emulsion preparation: At a temperature of 80℃, the aqueous phase solution is slowly added dropwise to the oil phase mixture. The dropwise addition process is accompanied by high-speed shear emulsification with a shear rate of 9000 r / min. After the aqueous phase is completely added, shearing continues for 9 min to obtain a water-in-oil emulsion.
[0059] Step 4, gradient curing: Transfer the emulsion to a cooling container equipped with a stirrer, turn on the stirrer at a speed of 110 r / min; reduce the system temperature from 78℃ to 55℃ at a cooling rate of 1.8℃ per minute, and stir for 13 min; continue to reduce the system temperature from 55℃ to 35℃ at a cooling rate of 1.0℃ per minute, and stir for 26 min to obtain semi-cured granular material.
[0060] Step 5, Granulation and Drying: The semi-cured granular material is granulated through a 24-mesh sieve and qualified granules are collected; the granules are placed in a hot air circulating oven and dried at 44℃ for 4.5 hours until the moisture content of the granules is 1.5%, thus obtaining porous waxy skeleton granules.
[0061] Step 6, total mixing and tableting: Weigh 18g of microcrystalline cellulose and 3g of magnesium stearate, mix them evenly with porous waxy skeleton particles, compress them into tablets, and the tablet weight is 220mg to obtain sustained-release tablets.
[0062] The sustained-release tablets obtained in this embodiment have a hardness of 7.8 kgf, a friability of 0.53%, and a content uniformity A+1.8S value of 8.7. Example 5:
[0063] Raw material formula: Metformin hydrochloride 85g, glyceryl behenate 72g, cetyl alcohol 24g, sorbitan monostearate 6g, polyethylene glycol 6000 16g, microcrystalline cellulose 15g, magnesium stearate 2g.
[0064] Preparation process: Step 1, oil phase preparation: Weigh 72g of behenicol and 24g of cetyl alcohol, place them in a sealed container heated in a water bath, heat to 80℃, and stir until completely melted; add 85g of metformin hydrochloride and 6g of sorbitan monostearate, and stir for 25min at 400r / min to obtain a uniformly dispersed oil phase mixture.
[0065] Step 2, Aqueous phase preparation: Weigh 16g of polyethylene glycol 6000, dissolve it in 48g of purified water to prepare a 25% (w / w) polyethylene glycol 6000 aqueous solution, heat to 78℃ and keep warm to obtain an aqueous solution.
[0066] Step 3, emulsion preparation: At a temperature of 79°C, the aqueous phase solution is slowly added dropwise to the oil phase mixture. The dropwise addition process is accompanied by high-speed shear emulsification with a shear rate of 10,000 r / min. After the aqueous phase is completely added, shearing continues for 7 min to obtain a water-in-oil emulsion.
[0067] Step 4, gradient curing: Transfer the emulsion to a cooling container equipped with a stirrer, turn on the stirrer at a speed of 115 r / min; reduce the system temperature from 77℃ to 55℃ at a cooling rate of 2.0℃ per minute, and keep stirring at this temperature for 12 min; continue to reduce the system temperature from 55℃ to 35℃ at a cooling rate of 1.0℃ per minute, and keep stirring at this temperature for 24 min to obtain semi-cured granular material.
[0068] Step 5, Granulation and Drying: The semi-cured granular material is granulated through a 24-mesh sieve and qualified granules are collected; the granules are placed in a hot air circulating oven and dried at 42℃ for 5 hours until the moisture content of the granules is 1.6%, thus obtaining porous waxy skeleton granules.
[0069] Step 6, total mixing and tableting: Weigh 15g of microcrystalline cellulose and 2g of magnesium stearate, mix them evenly with porous waxy matrix particles, compress them into tablets, and the tablet weight is 220mg to obtain sustained-release tablets.
[0070] The sustained-release tablets obtained in this embodiment have a hardness of 8.1 kgf, a friability of 0.44%, and a content uniformity A+1.8S value of 7.9.
[0071] Comparative Example 1: Raw material formula: Metformin hydrochloride 80g, glyceryl behenate 75g, cetyl alcohol 25g, polyethylene glycol 6000 15g, microcrystalline cellulose 22g, magnesium stearate 3g.
[0072] Preparation process: Weigh out 80g of metformin hydrochloride, 75g of glyceryl behenate, 25g of cetyl alcohol, and 15g of polyethylene glycol 6000. After passing all ingredients through a 60-mesh sieve, mix them thoroughly. Use a hot-melt method, placing the mixed powder in an 80℃ water bath and heating to melt, stirring for 30 minutes until uniform. After cooling and solidification, pulverize and granulate through a 24-mesh sieve. Dry at 42℃ for 5 hours to obtain waxy skeleton particles. Add 22g of microcrystalline cellulose and 3g of magnesium stearate, mix thoroughly, and compress into tablets with a tablet weight of 220mg.
[0073] This comparative example was prepared using a physical mixing and melting method, without the use of emulsifiers or an emulsion template pore-forming step. The resulting waxy framework particles lacked a uniform pore structure, and the pore-forming agent was randomly distributed in the framework in particle form.
[0074] Comparative Example 2: Raw material formula: Metformin hydrochloride 80g, glyceryl behenate 75g, cetyl alcohol 25g, sodium lauryl sulfate 6g, polyethylene glycol 6000 15g, microcrystalline cellulose 16g, magnesium stearate 3g.
[0075] Preparation process: Step 1, Aqueous phase preparation: Dissolve 80g of metformin hydrochloride and 15g of polyethylene glycol 6000 in 45g of purified water, heat to 78℃, add 6g of sodium dodecyl sulfate and stir to dissolve, thus obtaining an aqueous solution.
[0076] Step 2, oil phase preparation: Weigh 75g of behenicol glyceryl ester and 25g of cetyl alcohol, heat to 80℃ to melt, and obtain the oil phase.
[0077] Step 3, emulsion preparation: At 80℃, the oil phase is added dropwise to the aqueous phase and emulsified by high-speed shearing at 10000 r / min for 8 min to obtain an oil-in-water emulsion.
[0078] Step 4, curing and drying: Cool to 35℃ for curing, pulverize through a 24-mesh sieve for granulation, dry at 42℃ for 5 hours to obtain granules; add 16g of microcrystalline cellulose and 3g of magnesium stearate, mix evenly, compress into tablets, the tablet weight is 220mg, and the product is obtained.
[0079] This comparative example uses an oil-in-water emulsion with sodium dodecyl sulfate as the emulsifier, and the emulsion type is the opposite of that in this invention. The resulting particles contain mostly drug on the particle surface and outer layer, with a low drug content in the internal waxy framework.
[0080] Comparative Example 3: Raw material formula: Metformin hydrochloride 80g, glyceryl behenate 96g, polyethylene glycol 6000 15g, microcrystalline cellulose 26g, magnesium stearate 3g.
[0081] Preparation process: Step 1, oil phase preparation: Weigh 96g of behenicol glyceryl ester and heat to 80℃ to melt; add 80g of metformin hydrochloride, stir and disperse evenly to obtain an oil phase mixture.
[0082] Step 2, Aqueous phase preparation: Weigh 15g of polyethylene glycol 6000 and dissolve it in 45g of purified water, then heat to 78℃ to obtain an aqueous solution.
[0083] Step 3, emulsion preparation: At 80℃, the aqueous phase is added dropwise to the oil phase and emulsified by high-speed shearing at 10000 r / min for 8 min to obtain the emulsion.
[0084] Step 4, gradient curing: Curing is carried out according to the cooling process of Example 1. After granulation, the granules are dried at 42°C for 5 hours to obtain granules. 26g of microcrystalline cellulose and 3g of magnesium stearate are added and mixed evenly. The mixture is then compressed into tablets with a tablet weight of 220mg.
[0085] This comparative example used only a single wax material, glyceryl behenate, without adding cetyl alcohol for compounding, and no emulsifier was added. Due to the lack of an emulsifier, the system obtained in step three was an unstable coarse dispersion rather than a stable water-in-oil emulsion, with large and easily aggregated aqueous droplets. Due to the lack of the moderating effect of the low-melting-point wax component, the overall melting point of the skeleton was high, the curing rate was fast, the integrity of the pore structure was poor, and some pores collapsed.
[0086] Comparative Example 4: Raw material formula: Metformin hydrochloride 80g, hydroxypropyl methylcellulose K4M 45g, microcrystalline cellulose 70g, magnesium stearate 3g, povidone K30 2g.
[0087] Preparation process: Weigh out 80g of metformin hydrochloride, 45g of hydroxypropyl methylcellulose K4M, and 70g of microcrystalline cellulose, and mix them evenly. Use a 10% ethanol solution of povidone K30 as a binder and wet granulate. Dry at 45℃ until the moisture content is less than 3.0%, and granulate. Add 3g of magnesium stearate, mix evenly, and compress into tablets with a tablet weight of 200mg.
[0088] This comparative example is a hydrophilic gel matrix sustained-release tablet commonly used in existing technologies, prepared using hydroxypropyl methylcellulose K4M as the matrix material and a wet granulation and tableting process. Its sustained-release mechanism involves gel layer diffusion and matrix dissolution.
[0089] Comparative Example 5: Raw material formula: Metformin hydrochloride 80g, ethyl cellulose 20g, diethyl phthalate 3g, microcrystalline cellulose 94g, magnesium stearate 3g.
[0090] Preparation process: Weigh out 80g of metformin hydrochloride and 60g of microcrystalline cellulose, and mix them evenly. Dissolve 20g of ethyl cellulose and 3g of diethyl phthalate in 95% ethanol to prepare a 10% coating solution. Granulate and coat the mixed powder using a fluidized bed bottom spray process, with an inlet air temperature of 40℃ and a material temperature of 32℃. After drying the granules, granulate them, add the remaining 32g of microcrystalline cellulose and 2.5g of magnesium stearate, mix evenly, and compress into tablets with a tablet weight of 200mg.
[0091] This comparative example is a conventional insoluble matrix sustained-release tablet using ethyl cellulose as the insoluble matrix material, with the drug diffused and released through the matrix pores. This system is a simplified form of conventional membrane-controlled sustained-release formulations.
[0092] Comparative Example 6: Raw material formula: Metformin hydrochloride 80g, glyceryl behenate 75g, cetyl alcohol 25g, polyethylene glycol 6000 15g, microcrystalline cellulose 22g, magnesium stearate 3g.
[0093] Preparation process: Step 1, Melting and Dispersing: Heat 75g of behenicol and 25g of cetyl alcohol to 80℃ to melt, then add 80g of metformin hydrochloride and stir to disperse evenly.
[0094] Step 2, adding the pore-forming agent solution: Dissolve 15g of polyethylene glycol 6000 in 45g of purified water and heat to 78℃; add the polyethylene glycol aqueous solution to the molten material under stirring conditions, stirring at a speed of 400r / min for 10min.
[0095] Step 3, cooling and curing: Cool down to 35°C at a rate of 2.0°C per minute, then pulverize through a 24-mesh sieve to form granules, and dry at 42°C for 5 hours.
[0096] Step 4, total mixing and tableting: Add 16g of microcrystalline cellulose and 3g of magnesium stearate, mix well, compress into tablets, and the tablet weight is 220mg.
[0097] This comparative example combines the existing melt method with the addition of an aqueous pore-forming agent. In this method, the aqueous pore-forming agent is added to the molten wax phase under low-speed stirring, but a stable water-in-oil emulsion is not formed. The pore-forming agent is unevenly distributed in the system, and local agglomeration is obvious.
[0098] Comparative Example 7: Raw material formula: 80g of sucrose blank pellet core, 60g of metformin hydrochloride, 15g of ethyl cellulose, 6g of polyethylene glycol 6000, 8g of talc, 5g of hydroxypropyl methylcellulose, and 1.5g of magnesium stearate.
[0099] Preparation process: Step 1, drug application: Prepare a drug-containing suspension by mixing 60g of metformin hydrochloride and 5g of hydroxypropyl methylcellulose. Apply the drug to the sucrose blank pellet core using a fluidized bed bottom spray process. The air inlet temperature is 40℃ and the material temperature is 32℃. Dry the pellet after application.
[0100] Step 2, sustained-release coating: Prepare a coating solution by mixing 15g of ethyl cellulose, 60006g of polyethylene glycol, and 8g of talc. Coat the drug-containing pill core with sustained release coating. The coating weight increases by about 20%. Dry at 40°C for 2 hours after coating.
[0101] Step 3, filling: Mix the coated microcapsules with 1.5g of magnesium stearate and fill them into capsules, each containing 500mg of the drug.
[0102] This comparative example demonstrates a possible solution obtained by combining existing microsphere coating technology with pore-forming agents. This solution employs a membrane-controlled microsphere structure, adjusting the drug release rate through a pore-forming agent in the coating membrane, representing a mature method for preparing sustained-release microspheres in the prior art.
[0103] Performance testing: Release rate determination: The release rate was determined according to Method II (0931) of the General Chapter IV of the 2020 Chinese Pharmacopoeia, using the paddle method. The dissolution medium was 900 mL of pH 6.8 phosphate buffer, the rotation speed was 50 r / min, and the temperature was 37℃ ± 0.5℃. Samples of 5 mL were taken at 2 h, 6 h, 12 h, 18 h, and 24 h, and fresh dissolution medium of the same volume and temperature was added simultaneously. After filtration through a 0.45 μm microporous membrane, the drug concentration was determined by high-performance liquid chromatography (HPLC), and the cumulative release rate at each time point was calculated. HPLC conditions: C18 column, column temperature 30℃, mobile phase: methanol and pH 3.0 phosphate buffer at a volume ratio of 30:70, flow rate 1.0 mL / min, detection wavelength 233 nm, injection volume 20 μL.
[0104] Pore structure characterization: The pore morphology of the particle cross-section was observed using a scanning electron microscope. The pore size distribution was statistically analyzed using image analysis software, and the average pore size and pore size variation coefficient were calculated. No fewer than 200 pores were counted for each sample group.
[0105] Hardness testing: The hardness of tablets was measured using a tablet hardness tester. Ten tablets were randomly selected from each group, and the average value was taken.
[0106] Friability determination: determined according to General Chapter 0923 of Part IV of the 2020 edition of the Chinese Pharmacopoeia.
[0107] Content uniformity: determined according to General Chapter 0941 of Part IV of the 2020 edition of the Chinese Pharmacopoeia.
[0108] Table 1. Release rate test results:
[0109] Table 2 Test results of duct structure parameters: Note: The coefficient of variation of pore size in Comparative Example 1 is marked as "—" because Comparative Example 1 uses a physically mixed pore-forming agent, which has extremely large differences in pore size and irregular distribution. In addition, there are a large number of irregular large cavities formed by the aggregation of pore-forming agents. The pore size data does not show a normal distribution, and the coefficient of variation is not statistically significant, so it is not calculated.
[0110]
[0111] Results analysis: The 2-hour release rates of Examples 1 to 5 ranged from 8.7% to 11.9%, and the 24-hour release rates ranged from 92.3% to 95.3%. The zero-order release fitting correlation coefficient was greater than or equal to 0.978, indicating that the formulation of the present invention had a low initial burst release, complete release in the later stage, and a stable release process. Among them, Example 2 had a slightly slower release rate due to the higher amount of wax skeleton and the relatively lower amount of pore-forming agent; Example 3 had a slightly faster release rate due to the higher drug loading and the larger amount of pore-forming agent, with a 2-hour release rate of 11.9%, which was still within the low burst release range; in Example 4, the mass ratio of behenicol to cetyl alcohol was 4:1, the cetyl alcohol content was lower, the skeleton solidification rate was faster, the pore uniformity was slightly lower, and the release incompleteness was slightly increased, but it still met the requirements for sustained release. The average pore diameter of each example ranged from 13.5 μm to 21.6 μm, and the coefficient of variation of pore diameter ranged from 18.2% to 23.4%, indicating that the pore size distribution was uniform, and the emulsion template method achieved good pore structure control.
[0112] Comparative Example 1, using a physical mixing and melting method, achieved a release rate as high as 24.8% after 2 hours, exhibiting a significant burst release effect. This is because the pore-forming particles are enriched on the surface of the framework, rapidly dissolving upon contact with the release medium to form large pore channels, allowing a large amount of drug to be released quickly from the surface. Comparative Example 2, using an oil-in-water emulsion, achieved a release rate as high as 35.6% after 2 hours, exhibiting the most severe burst release. This is because the drug is dissolved in a continuous aqueous phase, and after solidification, the drug is mainly distributed on the particle surface and near the surface, with initial release not being effectively controlled. Comparative Example 3, using a single wax material, achieved a release rate of only 85.8% after 24 hours, indicating incomplete release. Furthermore, the coefficient of variation for pore size reached 42.8%, indicating poor pore uniformity. This demonstrates that the addition of hexadecyl alcohol plays a crucial role in regulating the crystallization behavior of the framework and maintaining the integrity of the pore structure.
[0113] Comparative Example 4, a hydrophilic gel matrix sheet, showed a 2-hour release rate of 18.9%, higher than that of the embodiments of the present invention. However, its zero-order fitting correlation coefficient for the release curve was 0.951, indicating that its release stability was not as good as that of the present invention. Comparative Example 5, an insoluble matrix sheet, showed a 24-hour release rate of only 89.7%, indicating incomplete release and a significant decrease in the release rate in the later stages. Comparative Example 6, a simple combination of the melt method and the pore-forming agent aqueous solution in the prior art, achieved a 2-hour release rate of 18.2%, significantly higher than that of the embodiments of the present invention. Furthermore, its pore size variation coefficient was as high as 58.4%, indicating that simply mixing the pore-forming agent aqueous solution could not form a uniform pore structure, and the technical effect of this method was significantly different from that of the present invention. Comparative Example 7, a membrane-controlled sustained-release microsphere, although achieving a zero-order fitting coefficient for the release curve of 0.962, still showed a 2-hour release rate of 14.6%, higher than most embodiments of the present invention. Moreover, this process requires fluidized bed coating equipment, resulting in a complex process flow and high production costs.
[0114] Comparative Examples 6 and 7 above represent two improvement paths that a person skilled in the art might conceive of based on the prior art: directly mixing the melt method with the aqueous solution of the pore-forming agent and using mature membrane-controlled coating technology.
[0115] However, formulations obtained through these two approaches are inferior to those of this invention in terms of burst release control and process simplicity. The technical approach of this invention, which constructs a uniform pore network using an emulsion template method, is not a simple superposition of existing technologies. The resulting technical effect of achieving both low burst release and high release completeness exceeds the reasonable expectations of those skilled in the art.
[0116] Furthermore, it should be particularly noted that the synergistic effect of low burst release, high release completeness, and high zero-order release characteristics described in this invention is the result of the combined effect of emulsion template pore-forming, wax-based composite framework, and gradient curing process, and cannot be achieved by a single technical feature. (1) The emulsion template method provides a structural basis for uniform pore distribution, but uniform pores alone are not enough to control the release behavior. If the skeleton material crystallizes too quickly, causing the pores to close, or crystallizes too slowly, causing the pores to deform, a stable sustained release effect cannot be achieved. (2) The combination of behenicol and cetyl alcohol provides a suitable temperature range and crystallization rate for the solidification of the skeleton. The synergistic effect of the two allows the wax skeleton to solidify gradually over a wide temperature range, providing a time window for the in-situ sealing of emulsion droplets. When behenicol is used alone (see Comparative Example 3), the skeleton crystallization rate is too fast, droplet aggregation is severe, and the uniformity of the pores is significantly reduced. (3) The gradient solidification process further regulates the kinetics of the skeleton solidification. In the first stage, rapid cooling forms a preliminary skeleton structure and fixes the droplet position. In the second stage, slow cooling allows the crystals to grow fully and perfect the pore wall structure. The two-stage cooling strategy matches the melting-solidification characteristics of the wax compound system, which together ensures the integrity of the pore structure and batch-to-batch consistency.
[0117] The three technical features described above are interdependent and synergistic, together constituting the core technical solution of this invention. Those skilled in the art, based on simple combinations or conventional optimizations of existing technologies, will find it difficult to achieve the comprehensive technical effects described in this invention.
[0118] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention.
Claims
1. A sustained-release pharmaceutical preparation, characterized in that, Based on total mass, the formulation is prepared from the following components in the following mass percentages: 20% to 40% active pharmaceutical ingredient, 35% to 60% waxy matrix material, 2% to 5% emulsifier, 5% to 10% pore-forming agent, 5% to 15% filler, and 0.5% to 2% lubricant; the waxy matrix material is composed of glyceryl behenate and cetyl alcohol in a mass ratio of 2:1 to 4:1; the emulsifier is sorbitan monostearate; the pore-forming agent is polyethylene glycol 6000; the sustained-release pharmaceutical preparation has a uniformly distributed pore structure with an average pore diameter of 5 μm to 30 μm and a pore diameter variation coefficient of less than 25%, and the pore walls are coated with the pore-forming agent.
2. The sustained-release pharmaceutical preparation according to claim 1, characterized in that, The mass ratio of behenicol to cetyl alcohol in the waxy skeleton material is 2.5:1 to 3.5:
1.
3. The sustained-release pharmaceutical preparation according to claim 1, characterized in that, The active pharmaceutical ingredient is metformin hydrochloride.
4. The sustained-release pharmaceutical preparation according to claim 1, characterized in that, The filler is microcrystalline cellulose, and the lubricant is magnesium stearate.
5. A method for preparing the sustained-release pharmaceutical formulation as described in claim 1, characterized in that, Includes the following steps: Step 1, Oil phase preparation: Weigh the prescribed amounts of glyceryl behenate and cetyl alcohol, place them in a sealed container heated in a water bath, heat to 78°C to 85°C, and stir until completely melted; add the prescribed amounts of active pharmaceutical ingredient and sorbitan monostearate, and stir at 300 r / min to 500 r / min for 20 min to 30 min to obtain a uniformly dispersed oil phase mixture; Step 2, Aqueous Phase Preparation: Weigh the prescribed amount of polyethylene glycol 6000, dissolve it in purified water to prepare a 20% to 35% (w / w) polyethylene glycol 6000 aqueous solution, heat to 75°C to 80°C and maintain the temperature to obtain an aqueous solution; wherein, the mass of purified water added is 30% to 50% of the total mass of the waxy skeleton material; Step 3, emulsion preparation: Under the temperature conditions of 78℃ to 82℃, the aqueous phase solution obtained in step 2 is slowly added dropwise to the oil phase mixture obtained in step 1. The dropwise addition process is accompanied by high-speed shear emulsification, with a shear rate of 8000 r / min to 12000 r / min. After the aqueous phase is completely added, shearing continues for 5 min to 10 min to obtain a water-in-oil emulsion. Step 4, gradient curing: Transfer the emulsion obtained in Step 3 to a cooling container equipped with a stirrer, turn on the stirrer at a speed of 80 r / min to 150 r / min; reduce the system temperature from 78°C to 55°C at a cooling rate of 1.5°C to 2.5°C per minute, and stir for 10 min to 15 min; continue to reduce the system temperature from 55°C to 35°C at a cooling rate of 0.8°C to 1.2°C per minute, and stir for 20 min to 30 min to obtain a semi-cured granular material; Step 5, Granulation and Drying: The semi-cured granular material obtained in Step 4 is granulated through a 24-mesh sieve and qualified granules are collected; the granules are placed in a hot air circulating oven and dried at 40℃ to 45℃ for 4 to 6 hours until the moisture content of the granules is less than 2.0%, thus obtaining porous waxy skeleton granules. Step 6, Total Mixing and Tableting: Weigh the prescribed amount of filler and lubricant, mix them evenly with the porous waxy matrix particles obtained in Step 5, and compress them into tablets to obtain the sustained-release pharmaceutical preparation.
6. The preparation method according to claim 5, characterized in that, In step three, the shear rate of high-speed shear emulsification is 9000 r / min to 11000 r / min, and the shearing time is 6 min to 8 min.
7. The preparation method according to claim 5, characterized in that, In step four, the cooling rate in the first stage is 1.8°C to 2.2°C per minute, and the cooling rate in the second stage is 0.9°C to 1.1°C per minute.
8. The preparation method according to claim 5, characterized in that, In step two, the mass concentration of the polyethylene glycol 6000 aqueous solution is 23% to 28%.
Citation Information
Patent Citations
Slow release preparation of ranitidine
CN101002739A
Sustained-release preparation of nicorandil
CN1994283A
